2014
DOI: 10.1093/gbe/evu057
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Fecundity and Shifts in Cellular Processes by a Native Virus on an Invasive Insect

Abstract: Pathogens and their vectors have coevolutionary histories that are intricately intertwined with their ecologies, environments, and genetic interactions. The soybean aphid, Aphis glycines, is native to East Asia but has quickly become one of the most important aphid pests in soybean-growing regions of North America. In this study, we used bioassays to examine the effects of feeding on soybean infected with a virus it vectors (Soybean mosaic virus [SMV]) and a virus it does not vector (Bean pod mottle virus [BPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 80 publications
0
26
0
Order By: Relevance
“…While the factors governing the temporal differences in the onset of diminished fecundity between the virus‐infected treatments are unknown, a potential molecular signature could be observed in the aphid transcriptional profiles of Cassone et al . (). In that study, the downregulation of the transcriptome and associated significant reduction in fecundity were detected considerably earlier in the BPMV treatment.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…While the factors governing the temporal differences in the onset of diminished fecundity between the virus‐infected treatments are unknown, a potential molecular signature could be observed in the aphid transcriptional profiles of Cassone et al . (). In that study, the downregulation of the transcriptome and associated significant reduction in fecundity were detected considerably earlier in the BPMV treatment.…”
Section: Discussionmentioning
confidence: 52%
“…We initially hypothesized that aphid host feeding on BPMV‐infected soybean detrimentally impacted Buchnera , which in turn altered aphid fecundity. Our previous study indicated Buchnera density was lower in aphids fed on both BPMV‐infected and SMV‐infected soybean but decreased fecundity was only detected in the BPMV treatment (Cassone et al ., ); however, by extending the fitness assays to include an additional 10‐day period, reductions in fecundity were also evident in the aphids feeding on SMV‐infected plants. While the factors governing the temporal differences in the onset of diminished fecundity between the virus‐infected treatments are unknown, a potential molecular signature could be observed in the aphid transcriptional profiles of Cassone et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations